Polarization-insensitive unidirectional spoof surface plasmon polaritons coupling by gradient metasurface - 施宏宇 张安学 陈建忠 王甲富 夏颂 徐卓 (Chinese physics B, 2016)
A polarization-insensitive unidirectional spoof surface plasmon polariton（SPP） coupler mediated by a gradient metasurface is proposed. The field distributions and average Poynting vector of the coupled spoof SPPs are analyzed. The simulated and experimental results support the theoretical analysis and indicate that the designed gradient metasurface can couple both the parallel-polarized and normally-polarized incident waves to the spoof SPPs propagating in the same direction at about 5 GHz.